Omics technologies and bio-engineering : towards improving quality of life - Barh, Debmalya; Azevedo, Vasco (Emerging fields, animal and medical biotechnologies, 2018)
Omics Technologies and Bio-Engineering: Towards Improving Quality of Life, Volume 1 is a unique reference that brings together multiple perspectives on omics research, providing in-depth analysis and insights from an international team of authors. The book delivers pivotal information that will inform and improve medical and biological research by helping readers gain more direct access to analytic data, an increased understanding on data evaluation, and a comprehensive picture on how to use omics data in molecular biology, biotechnology and human health care.